The Oxford handbook of Dewey - Fesmire, Steven 1967- (New York Oxford University Press, 2019)
"John Dewey was the foremost philosophical figure and public intellectual in early to mid-twentieth century America. He is still the most academically cited Anglophone philosopher of the past century, and is among the most cited Americans of any century. In this comprehensive volume spanning thirty-five chapters, leading scholars help researchers access particular aspects of Dewey's thought, navigate the enormous and rapidly developing literature, and participate in current scholarship in light of prospects in key topical areas. Beginning with a framing essay by Philip Kitcher calling for a transformation of philosophical research inspired by Dewey, contributors interpret, appraise, and critique Dewey's philosophy under the following headings: Metaphysics;0Epistemology, Science, Language, and Mind; Ethics, Law, and the Starting Point; Social and Political Philosophy, Race, and Feminist Philosophy; Philosophy of Education; Aesthetics; Instrumental Logic, Philosophy of Technology, and the Unfinished Project of Modernity; Dewey in Cross-Cultural Dialogue; The American Philosophical Tradition, the Social Sciences, and Religion; and Public Philosophy and Practical Ethics."-- Provided by publisher.
The Future of Philosophical Research -- Metaphysics -- Epistemology, Science, Language, and Mind -- Ethics, Law, and the Starting Point -- Social and Political Philosophy, Race, and Feminist Philosophy -- Philosophy of Education -- Aesthetics -- Instrumental Logic, Philosophy of Technology, and the Unfinished Project of Modernity -- Dewey in Cross-Cultural Dialogue -- The American Philosophical Tradition, the Social Sciences, and Religion -- Public Philosophy and Practical Ethics.
Includes bibliographical references and index.
Keywords: Dewey, John -- 1859-1952.